2018
DOI: 10.1016/j.apacoust.2018.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic response from microscopic antibubbles

Abstract: An antibubble is a gas bubble containing a liquid droplet core. Both the droplet and the gas bubble are typically surrounded by stabilising shells. Owing to electrostatic forces exerted by these shells, core droplets of micrometer diameter do not readily coalesce with the surrounding liquid medium. Owing to the incompressibility of the liquid droplet core, antibubbles will oscillate asymmetrically, i.e., the radial excursion amplitude of the surface is greater during expansion than during contraction, when sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Noticeably, it has recently been suggested that leaks from subsea hydrocarbon production facilities contain antibubbles with a specific acoustic signature [5]. Nowadays, benefiting from the development of microfluidics, several potential applications have arisen, such as using antibubbles as contrast agent for enhancing ultrasonic imaging [6,7] or loading the antibubble core with a ferrofluid to serve as a vehicle for magneto-controlled drug delivery [8].…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, it has recently been suggested that leaks from subsea hydrocarbon production facilities contain antibubbles with a specific acoustic signature [5]. Nowadays, benefiting from the development of microfluidics, several potential applications have arisen, such as using antibubbles as contrast agent for enhancing ultrasonic imaging [6,7] or loading the antibubble core with a ferrofluid to serve as a vehicle for magneto-controlled drug delivery [8].…”
Section: Introductionmentioning
confidence: 99%
“…The silica particles on the outer interface have been reported to form a single elastic layer. 22) The same batch of the antibubbles used to create Figure 1 has been used for the experiments described in this paper.…”
mentioning
confidence: 99%
“…Two media containing (anti)bubbles were prepared for evaluation, as previously published. 18,22) For stabilisation, Aerosil ® R972 hydrophobised silica particles (Evonik Industries AG, Essen, Germany) were used. 22) For the first medium, hereafter referred to as AB, the aqueous cores were replaced by 2 vol% of hydrophobically modified Zano 10 Plus zinc oxide nanoparticles (Umicore, Brussel, Belgium).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The session on bubbles, antibubbles, and droplets was chaired by Christine Contino-Pépin from the University of Avignon and Charles Sennoga from the University of Tours. Invited speaker Albert Poortinga from Eindhoven University of Technology lectured on a new kind of acoustic bubble, called the antibubble [15,16]. Steven Wrenn from Drexel University presented a voltage-activated ultrasound contrast agent for myocardial perfusion imaging [17].…”
mentioning
confidence: 99%